Recovery of gold from refractory ore employing pressure oxidation - Flávio de Almeida Lemos; Marisa Nascimento; Gaspar Rodrigues Moreira Júnior; Vanessa Resende de Andrade; Paul Cezanne Pinto; Afonso José Guedes Salles (REM: International Engineering Journal)
Abstract The extraction of gold from refractory gold mineral deposits is becoming increasingly necessary. The presence of gold encapsulated within the crystalline matrix of iron sulfide minerals, such as pyrite, pyrrhotite, and arsenopyrite significantly reduces the efficiency of cyanidation. Therefore, the use of oxidative pretreatments, such as calcination, pressure oxidation, or bacterial leaching, enables a high gold recovery from refractory deposits. Calcination has been widely employed. However, it has a high energy cost and environmental issues due to the release of toxic gases containing arsenic. In the treatment of refractory gold ores containing arsenic, pressure oxidation (POX) represents an attractive approach for arsenic immobilization, since the conditions are suitable for both sulfide oxidation and the formation of stable arsenates. In the present study, tests of alkaline and acidic pressure oxidation followed by sodium cyanide leaching were conducted on a composite sample of the Faina Project, owned by Jaguar Mining Inc., located in de northwest portion of the Iron Quadrangle, Minas Gerais, Brazil. The mineralization is hosted by metabasalts and komatiitics metabasalts of an archean metavulcano sedimentary sequence, in the Greenstonebelt Pitangui. The tests demonstrated that it is possible to achieve a 98.40% gold recovery using a concentrate initially containing 12% sulfur, which underwent acidic oxidation with a 0.28 M H2SO4 solution at a temperature of 220°C, oxygen pressure of 500 kPa, and a residence time of three hours. This result was 19.19% higher than that obtained in an alkaline medium using a 3.0 M NaOH solution.